2009
DOI: 10.18553/jmcp.2009.15.5.420
|View full text |Cite
|
Sign up to set email alerts
|

Examination of MTM Opportunities in Pediatric Behavioral Health

Abstract: HealthWe performed a retrospective and exploratory chart review, based on a convenience sample, to assess the need for medication-related services in a primarily child and adolescent, nonMedicare population served by a private, ambulatory behavioral center providing primarily outpatient psychiatry, psychotherapy, and partial hospitalization services. We (a) collected demographic data; (b) defined eligibility for a potential MTM program for this patient population based on criteria that were derived from CMS, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In the Medicare population, eligibility for MTM requires (at a minimum) that beneficiaries meet the following criteria: (1) the presence of multiple chronic diseases; (2) take multiple prescription medications; and (3) incur a specified dollar amount for covered Part D drugs. Since pediatric patients are not beneficiaries of Medicare, implementation of MTM for this population has been limited [6,7]. …”
Section: Medication Therapy Managementmentioning
confidence: 99%
“…In the Medicare population, eligibility for MTM requires (at a minimum) that beneficiaries meet the following criteria: (1) the presence of multiple chronic diseases; (2) take multiple prescription medications; and (3) incur a specified dollar amount for covered Part D drugs. Since pediatric patients are not beneficiaries of Medicare, implementation of MTM for this population has been limited [6,7]. …”
Section: Medication Therapy Managementmentioning
confidence: 99%
“…The study highlights the opportunity for pharmacist involvement in optimizing medication use in pediatrics. 16 Medication reconciliation is required by the Joint Commission when a patient has a transition of care across the health care continuum in an effort to prevent medication errors including duplication of therapy, omission of medications, inappropriate dosing, and drug interactions. 17 One study using a pharmacist to complete medication reconciliation in an emergency department found that nearly 80% of patients' medication histories had an omission of a dose and 25% had an omission of a specific prescribed medication.…”
Section: Ppaca and Pharmacists In Pediatric Practicementioning
confidence: 99%